Thermodynamics and London office property cycles. Issue 3 (3rd April 2018) - Szweizer, Moshe
Abstract : Purpose: The purpose of this paper is to extend the studies of commercial property cycles by providing a cross-field approach to property markets modelling. Design/methodology/approach: The approach allows for the incorporation of market shocks into the property cycle model as fundamental building blocks; assessment of overall market absorption generated through cyclic activity; and timing estimation of major market events. An ideal model is first constructed, which relies on an observation that a property cycle consists of four distinctive phases. These are described formally through appropriate formulae. Subsequently, it is observed that an analogous cyclic behaviour is described in physics as the Otto cycle. The formulae derived in physics for the Otto cycle are now redefined so to be applicable to the property market. Findings: The model has been applied to the London office market, both to the historic and the current data sets. This allowed for the comparison of model predicted absorption and vacancies with the historic records, providing for assessment of the model accuracy. The model predicted that absorption was also compared with historic space supply allowing for estimation of oversupply and resultant vacancies. London office submarkets were analysed and compared to each other, allowing for estimation of their relative attractiveness as perceived by tenants and developers. Practical implications: The model may be used to estimate cycle generated absorption; therefore, over and under supply of space due to developers' activity may be assessed. It is also possible to use the model to assess the timing of future market peaks and troughs. Originality/value: This is the first research directly applying the methodology developed in physics to commercial property cycles.